1981
DOI: 10.1161/01.cir.64.6.1277
|View full text |Cite
|
Sign up to set email alerts
|

Site of antegrade and retrograde functional right bundle branch block in the intact canine heart.

Abstract: SUMMARY The purpose of this study was to determine the site of conduction delay or block in situ during antegrade and retrograde functional right bundle branch block (FRBBB) and whether reentrant excitation can occur in both directions in the blocked bundle branch, depending on whether the site of block occurred proximally or distally. Studies were performed in 20 adult mongrel dogs during cardiopulmonary bypass, using direct endocardial extracellular bipolar recordings of activaation in the His-Purkinje syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1982
1982
2001
2001

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…2 D) (Fig. 2 E) (3,17,23,24), although the present study cannot exclude a site within the HB (with longitudinal dissociation (25)(26)(27)(28). Studies in man have suggested (17,(29)(30)(31)(32), and canine studies by Moe et as was seen in this study.…”
Section: Resultssupporting
confidence: 40%
“…2 D) (Fig. 2 E) (3,17,23,24), although the present study cannot exclude a site within the HB (with longitudinal dissociation (25)(26)(27)(28). Studies in man have suggested (17,(29)(30)(31)(32), and canine studies by Moe et as was seen in this study.…”
Section: Resultssupporting
confidence: 40%
“…Persistence of anterograde functional block of one bundle branch due to repetitive retrograde concealed conduction of impulses propagating from the contralateral bundle branch initially was postulated by Gouaux and Ashman 1 in 1947 and subsequently corroborated experimentally by Moe et al 2 and by Glassman and Zipes. 3 This electrophysiologic phenomenon was termed a "linking" by Rosenbaum et al 4 in 1972. The term "linking" now is used to describe a general phenomenon in which functional block in one limb of a reentrant circuit is dynamically maintained by repetitive impulse interference or by repetitive impulse collision.…”
Section: Introductionmentioning
confidence: 99%